Success of Two Caries Risk Assessment Tools in Children: A Pilot Study With a 3-Year Follow-Up. (July 2020) - Kuru, Elif; Eden, Ece
Caries risk is defined as the dental caries probability under the individual bacteriological environment, dietary habits, and environmental factors. Assessment of caries risk plays a major role in the prevention of dental caries. The aim of this study was to compare the effectiveness of two different caries risk assessment methods on caries-free preschool children. A sample of 90 caries-free 4- to 6-year-old children were selected from 400 preschool children. The selection was limited to children who had no dental caries, visible plaque, and systemic disease. American Academy of Pediatric Dentistry's Caries Risk Assessment Tool (CAT) and Clinpro Cario L-Pop (CCLP; 3M ESPE, Germany) were used to categorize children into caries risk groups. Children were classified as being in high-, medium-, or low-risk groups by two methods. Determining risk factors according to CAT were examined. The compliance among the two methods was evaluated. Sixty-eight children were reevaluated intraorally after 3 years. The compliance between CAT and CCLP was sought using Kappa test. Statistical evaluation revealed moderate compliance among methods at baseline. The three most determinant factors in the high-risk group according to CAT were no topical fluoride exposure, no use of dental services, and active caries in mother . CAT is found statistically more successful than CCLP in predicting caries risk 3 years later. Caries risk assessment is effective to predict future caries and can be helpful for the clinician to choose the right tailor-made caries prevention plans.